Discourse Analysis of Social Antagonism in Pramoedya Ananta Toer's Nyanyi Sunyi Seorang Bisu - Asprida, Eka; Rumalean, Iwan; Solissa, Everhard Markiano (Universitas Pattimura, 2024)
The purpose of this study is to describe the discourse of social antagonism in Pramoedya Ananta Toer's work in the book Nyanyi Sunyi Sebuah Bisu. The method in this study is descriptive qualitative research analysis intends to describe and analyze the social antagonism present in Pramoedya Ananta Toer's letters in the novel Nyanyi Suyi Sebuah Bisu. The data in this study is social antagonism in the novel Nyanyi Sunyi Sebuah Bisu by Pramoedya Ananta Toer. While the data source used is the novel Nyanyi Sunyi Sebuah Bisu which contains 12 letters. The data collection techniques used are reading techniques and note-taking techniques. The reading technique is used to read the entire discourse text in the book Nyanyi Sunyi Sebuah Bisu. The note-taking technique is used to record data from the findings after carrying out the reading process. The results of this study are the discovery of a discourse of social antagonism where the discourses put forward by Pram then give rise to a new identity that forms his original identity. The analysis techniques used are data reduction, data presentation, conclusions. Data reduction is the process of selecting data and focusing on the level of simplification, abstraction, and translating data obtained from field note sheets. Data presentation can be in the form of writing or words. While the conclusion is a series of structured information that triggers drawing conclusions and choosing actions.